Transformasi e-administrasi jurusan Pendidikan Ekonomi dan pengaruhnya terhadap efisiensi dan kualitas pembelajaran - Arsana, I Kadek Satria; Afnita, Vinda; Hutahaean, Lidia Aprileny; Gintulangi, Sabriana Oktaviana (MAN 4 Kota Pekanbaru, 2025)
This study examines the effect of e-administration transformation on learning quality, with administrative efficiency serving as a mediating variable in the context of higher education. Using a SEM-PLS approach, data were collected from 179 respondents comprising lecturers, academic administrative staff, and students through random sampling. The findings confirm that e-administration transformation significantly enhances administrative efficiency, which in turn exerts a strong positive impact on learning quality. Furthermore, administrative efficiency partially mediates the relationship between e-administration transformation and learning quality, underscoring its strategic role as a driver of digital transformation. This study contributes to the development of the digital administrative transformation framework, offering theoretical novelty by integrating administrative efficiency with pedagogical quality improvement. Practically, the findings provide valuable insights for higher education institutions to redesign administrative systems that not only improve efficiency but also directly strengthen learning quality in the era of digital transformation.